OPTIMIZATION OF THE BUSINESS PROCESS FOR THE PROVISION OF LAND FOR THE CONSTRUCTION FACILITIES - Salmanova, R.; Ismailova, R. (Scientific Journal of Pedagogy and Economics, 2020)
The issue of efficient use of the land, as well as obtaining land from the government is one of the urgent issues in Kazakhstan. The article assesses the current system of public services “Provision of a land plot for the construction of a facility within the boundaries of a populated locality” This public service is provided for the construction of social facilities or the implementation of investor projects that are necessary for economic development. During the analysis, problems such as duplication of functions made by state bodies, dysfunctional system of request according to the principle of “One window”, bureaucracy for the consideration and the approval of a package of documents for granting the land plot were identified. To solve these problems, it was proposed to optimize the business processes of the public service “Provision of a land plot for the construction of a facility within the boundaries of a populated locality”, which allowed reducing the time, excluding duplicate functions, and increasing the transparency of the activities of state bodies.